A new perspective of the risk of caustic substance ingestion: the outcomes of 468 patients in one North Taiwan medical center within 20 years. (4th May 2021) - Chen, Yu-Jhou; Seak, Chen-June; Kang, Shih-Ching; Chen, Tsung-Hsing; Chen, Chien-Cheng; Ng, Chip-Jin; Lee, Chao-Wei; Su, Ming-Yao; Huang, Hsin-Chih; Chen, Pin-Cheng; Ooyang, Chun-Hsiang; Hsieh, Sen-Yung; et al.
Abstract: Introduction: Caustic substance ingestion is frequently life-threatening, and its pathological mechanisms of tissue damage are well documented. However, few studies have assessed the combined effects of pH and the ingested dose on patient outcomes. Additionally, the miscellaneous chemical properties are not immediately available for providing predictive insights to physicians. This study aimed to provide a new perspective of the risk assessment of caustic substance ingestion based on the pH and dose. Methods: The retrospective study analyzed adults treated for caustic substance ingestion at Chang Gung Memorial Hospital between January 1999 and December 2018. Uniformly strict inclusion/exclusion criteria and a double-checked process during chart review were adopted. All patients underwent urgent esophagogastroduodenoscopy (EGD) within 24 h. Caustic mucosal damage was graded using Zargar's modified endoscopic classification. The pH and ingested dose of caustic substances were clearly recorded. Statistical analyses were conducted using IBM SPSS, version 22. Results: Based on the 468 enrolled cases, the pH and dose were valuable predictors of the extent of gastrointestinal tract injury, commonly encountered complications, and long-term overall survival outcomes. Risks of mortality and perforation were dose-dependent for acids and pH-dependent for alkalis. The severe EGD findings (grade ≥ 2b) in this study were pH-dependent for both substances and additionally dose-dependent for acids. Conclusion: Combining pH and dose, we proposed a new perspective for the risk assessment of caustic substance ingestion. Such findings may provide predictive insights for resolving clinical uncertainty before the availability of examination results. "Large doses of acids" and "high pH of alkalis" deserve special attention. This new perspective with a retrospective nature requires further validation.